Lower back pain caused by radiculopathy induced by lumbar stenosis - literature review - Michał Turek; Aleksandra Winiarz; Paula Szlendak; Katarzyna Toś; Kacper Wojtala; Sylwia Grosman; Agata Węgrzyniak; Dominik Drobek; Katarzyna Wąsala; Wojciech Wokurka (Kazimierz Wielki University, 2023)
Introduction: Lumbar spine pain is a common clinical problem. Due to the multitude of causes of pain, it is important to know the most common ones in order to choose an effective method of treatment.  The aim of this study: Summary of current knowledge regarding back pain caused by radiculopathy associated with lumbar stenosis.  Material and method: The review includes publications published in 1995-2020. The search of the publications in the Pubmed database was carried out using the following keywords: back pain, radiculopathy, lumbar stenosis. Description of the stage of the knowledge: Lumbar radiculopathy caused by lumbar stenosis is a common clinical problem, especially in older age groups. In diagnostics, an interview with the patient, physical examination and imaging tests - especially CT and MRI - are important. In most patients, conservative treatment is sufficient - the use of analgesics and anti-inflammatory drugs and physiotherapy. In justified cases, surgical treatment should be considered as the most effective causative treatment of the disease. In the last 20 years, the availability of both diagnostic methods has increased and new surgical techniques have appeared, aiming at minimally invasive treatment. Summary: Radiculopathy caused by lumbar stenosis is a contributing factor to the occurrence of pain, which can hinder the normal functioning of the patient.Proper diagnosis, identification of the impact and methods of treatment, both conservative and surgical, can help the patient and affect his quality of life. Early diagnosis and treatment are crucial for the effective treatment of pain associated with radiculopathy caused by lumbar stenosis.